1992
DOI: 10.2307/2426545
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Small Mammal Community in a Fragmented Forest

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. The University of Notre Dame is collaborating with JSTOR to digitize, preserve and extend access to American Midland Naturalist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 30 publications
2
58
0
2
Order By: Relevance
“…Several studies indicate the higher densities in the habitat patches in more fragmented habitats (Chalfoun et al 2002), for example, in the case of the white-footed mice (Yahner 1992;Swihart 1996, 2000). Also, the study of Collins and Barrett (1997) on meadow voles showed that especially the densities of females were substantially higher in the fragmented habitats compared to nonfragmented ones.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate the higher densities in the habitat patches in more fragmented habitats (Chalfoun et al 2002), for example, in the case of the white-footed mice (Yahner 1992;Swihart 1996, 2000). Also, the study of Collins and Barrett (1997) on meadow voles showed that especially the densities of females were substantially higher in the fragmented habitats compared to nonfragmented ones.…”
Section: Discussionmentioning
confidence: 99%
“…Increased population densities represent one manifestation of the island syndrome in small mammals (e.g., Yahner 1992;Adler and Levins 1994), although the causes of these increases are not yet clear (Dooley and Bowers 1998;Langlois et al 2001). In accordance with prior findings, population densities in our study were much higher within forest fragments than within the continuous forest (four individuals/ha; Ruf et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…White-footed mice, primary reservoirs for B. burgdorferi, thrive in most forest environments. However, as an opportunistic species, whitefooted mice outcompete other small mammals in disrupted areas of small, fragmented forests, which are created when larger forests are subdivided as a result of land use changes (Yahner 1992). Therefore, the ecotone between forested and open, vegetated areas supports populations of both white-tailed deer and white-footed mice (Despommier et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The fragmentation of habitats of the species involved in Lyme disease transmission was found to be ''of pivotal importance'' by EstradaPena (2009, p. 153), when examining how rates of infected ticks varied in an endemic area. The significance of forest fragments more specifically was studied by Yahner (1992) who examined the relative abundance of white-footed mice, B. burgdorferi's most competent reservoir, in clearcut environments. He found that the relative abundance of white-footed mice as compared to other small mammals increased as the size of forest fragments decreased.…”
Section: Introductionmentioning
confidence: 99%